Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol